Balancing Life History Investment Decisions in Founding Ant Queens - Tragust, Simon; Brinker, Pina; Rossel, Natacha; Otti, Oliver (Frontiers in Ecology and Evolution, 2020)
Reproduction is a very critical step in the life of an organism. Females must balance their investment in different life-history traits while reproducing. During the process of colony founding in social organisms, such as ants or bees, a trade-off between reproduction and immunity might be very stringent, because queens might be constrained to invest into immune protection of themselves and their developing offspring until the first workers emerge. Here we investigate how different levels of microbial pressure affect colony founding success of Lasius niger ant queens and whether investment into immune defense traits comes at a substantial cost to the queens. In a first experiment mated queens were exposed to four different environments: sterile housing, autoclaved soil, untreated soil and soil containing two opportunistic pathogens. In this experiment, we investigated an immediate cost, i.e. the success of producing the first brood, and a potential delayed cost, i.e. queen survival and colony founding success after hibernation. For the latter, we removed the first brood after hibernation to reveal hidden costs via the application of an additional stressor. We found that irrespective of the microbial environment all queens successfully managed to start a colony, with queens in the soil treatments showing a higher worker production than the queens in the sterile environment. This suggests that either soil components or soil microbes benefit colony growth. After hibernation queens in microbe soil showed significantly lower survival and could not replace a lost brood. In a second experiment, we investigated whether external immune defense in the form of formic acid use can explain part of the costs imposed on queens. We found that queens used formic acid to sanitize their new nest suggesting that queens founding a colony under high microbial pressure are forced to pay a substantial cost by investing in both reproduction and immunity simultaneously. Our results suggest that early, simultaneous investment in reproduction and immunity can allow colony growth under microbial pressure but may be costly in terms of resistance to later challenges. Ant queens may thus be trading off insurance against future challenges for increased pathogen immunity.